Expression of an interleukin-2 partial agonist enhances regulatory T cell persistence and efficacy in mouse autoimmune models - Janie Robert; Manon Feuillolay; María de Temple-Llavero; Reginald Florian Akossi; Vanessa Mhanna; Mustapha Cheraï; Gwladys Fourcade; Frédéric Charlotte; Nicolas Tchitchek; Tian Mi; Benjamin Youngblood; Thomas Vazquez; et al. (Nature Communications)
Abstract Regulatory T (Treg)-based cell therapy holds promise for autoimmune and inflammatory diseases, yet challenges remain regarding the functional stability and persistence of transferred Tregs. Here we engineer Tregs to express a partial agonist form of IL-2 (IL-2pa) to enhance persistence while avoiding toxicity from excessive signaling. Mouse Tregs expressing wild-type IL-2 (Tregs-IL2wt) have only a transient growth advantage, limited by toxicity from likely excessive signaling. By contrast, mouse Tregs-IL2pa exhibit sustained expansion, long-term survival in immunocompetent mice for over a year, and bystander expansion of endogenous Tregs. Tregs-IL2pa maintain a stable activated phenotype, Treg-specific demethylation, and a diverse TCR repertoire. In vivo, prophylactic transfer of Tregs-IL2pa ameliorates multi-organ autoimmunity in a Treg depletion-induced mouse autoimmune model. Lastly, compared with control Treg, human Tregs-IL2pa show enhanced survival in the IL-2-depleted environment of immune-deficient mice and improved control of xenogeneic graft-versus-host disease. Our results thus show that IL-2pa self-sufficiency enhances the stability, durability and efficacy of Treg therapies in preclinical settings.